Pengaruh Pengendalian Internal, Komitmen Organisasi dan Budaya Organisasi Terhadap Pencegahan Fraud di Puskesmas Rumbai Barat - Rahayu Wulandari (Fakultas Ekonomi Universitas 45 Surabaya, 2024)
Fraud or Fraud is a crucial problem that always arises in organizations both profit and non-profit organizations, fraud itself is an act intentionally for certain purposes such as manipulating or providing false information to other parties or providing opposing or unlawful reports to gain benefits for themselves or for other parties. Fraud can occur anywhere, can be done by anyone and has an impact on anyone who can harm all parties either directly or indirectly